Management of development program for international companies’ in turbulence environment - Bushuyev, S.; Minayeva, T. (НТУ "ХПИ", 2015)
Theoretical aspects and elements of the methodology for modeling business environment international company based on the value-added chain (value) for interested parties should take into account the socio-economic, infrastructural and market components. We investigate the construction of such a business strategy of the international company that provides commercial, economic, fiscal and social efficiency of its activities on the basis of the selection of activities that bring the highest added value.
Keywords: value; value-added chain; international company; simulation; strategy